Talking really does matter: Lay perspectives from older people on talking about suicide in later life - Trish Hafford-Letchfield; Jeffrey R. Hanna; Toby J. Ellmers; Susan Rasmussen; Nicola Cogan; Helen Gleeson; Jolie Goodman; Sophie Martin; Patrick Walker; Matthew Quaife (Frontiers in Psychology, 2022)
BackgroundThe cumulative body of research on suicidality in later life describes its unique and complex features in older people when compared with that in other population groups. Yet significant gaps exist in how research informs the further development of suitable interventions. The perspectives of older people are also limited in research findings.AimsTherefore, this exploratory study aimed to (1) identify potential barriers and enablers in discussing suicidal thoughts and their expression in later life from the perspectives of lay older people and (2) explore where opportunities might occur in approach, place, relationships, and language with older people to discuss suicidal thoughts and their expression.MethodWe conducted in-depth qualitative individual interviews with 15 people aged 70–89 years. This method helped explore older peoples' own lay perspectives on suicidal thoughts in later life and how these are expressed, and their understanding of where and how people might seek support.ResultsA total of three themes were generated from the dataset: (1) intergenerational and socio-cultural differences in suicide expression, (2) the normalization of suicidal thoughts in later life, and (3) the importance and difficulties of everyday discussion and opportunities to express suicidal thoughts.ConclusionSuicidal thoughts and their expression appear commonly and are normalized in later life yet remain taboo and hidden. The participants revealed how such thoughts and behaviors are typically expressed through colloquial or “off-hand” remarks and comments and the importance of authentic listening. The findings highlight the importance of more informal discussions around these topics and how care professionals, practitioners, and providers might frame opportunities for dialogue with people who may want to access support. Further engagement with community-informed participatory research methods in which older people provide their own perspectives and experiences is important in addressing these gaps. There is a need for co-designing in developing screening, assessment, and signposting outside of clinical settings that can be used in everyday caring relationships with people in later life.